Development of prototype electronic dashboard service performance of LPKA class I Palembang - Hadiwijaya, Hendra; Febrianty, Febrianty; Azdy , Rezania Agramanisti (Sinkron : jurnal dan penelitian teknik informatika, 2021)
LPKA Palembang provides services to the community in the form of coaching in the fields of education, skills training, community guidance, and alleviation, services for Andikpas visits and complaints, remission submission services, assimilation, and other submissions especially to support alleviation programs such as the Conditional Leave (CB) program, Leaving Towards Free (CMB), and Parole (PB). To provide the best convenience and quality in providing services, a system is needed that can not only be used to submit and process service data online, but also can integrate service data so that it can be more easily accessed anytime and anywhere. The system created is an electronic dashboard or e-dashboard that can present data visually so that it is easily understood by readers. This study aims to build a prototype that can provide an overview of the e-dashboard system to be built. From the prototype evaluation, user feedback can be obtained which can be used to build an actual e-dashboard system so that it can reduce deviations from the system being built. The stages in this research are planning, designing, building, and evaluating the prototype. The results of this study are the development of e-Dashboard prototype that had been tested by 80% of LPKA Class I Palembang employees. The developed prototype has features that almost meet user needs because the system development is based on a quick analysis of the needs of future e-Dashboard users.